(untitled) (Fiep Bulletin - online, 2014)
Down Syndrome (DS) is the most common and well known of the malforming syndromes in the human species, being the first identified chromosomic aneuplodia in humans which can be characterized by the trissomy of pair 21. Amongst the many alterations found in the carriers of this pathology, they present a delay in the acquisition of the motor standards. This study consists of an analysis of free marching in down syndrome children carriers after physiotherapy release. This was a field research of combined exploratory-descriptive types having a sample consisting of 10 down syndrome children carriers, and a comparative group, formed by 10 children presenting normal development, both of ages ranging from 3 to 7 years. A board was used where marching would take place, that was painted in its inferior face to be marked the steps in bristol board; data with regards to time and distance were written down for posterior analysis. For the analysis of the results obtained, A Test t Student with significance level of up to 5% was used (p<0.05). After the results were evaluated, it was possible to infer that it did not present significant statistical differences in the lengths of the right-left steps; it presented statistical significance in the comparison of the average values of steps, passing, cadence, speed. Therefore, it has been noted, in the evaluated sample, that although the children had reached the independent deambulation and had been released from treatment, they had not acquired maturity of the marching standards. It is suggested then, that, in the process of treatment release, to be considered not only the fact that the child has the ability to perform accoring to standards, but also an analysis approaching their quantitative and qualitative aspects, thus preventing from making decisions solely based on observation.